«A pezzi. A pezzetti. A pezzettini»: the anecdote in contemporary Italian poetry - Giuliana Pala (Finzioni, 2023)
The following contribution examines the possibility of a revival of the ‘anecdote’ in contemporary Italian poetry. After introducing the notion of short forms (Montandon, 2001) or simple forms (Jolles, 1930) we will focus on the anecdote’s features and its use within three collections of contemporary Italian poetry, respectively: Le fuggitive by Carmen Gallo, Fuoco degli occhi by Marilena Renda and Betelgeuse e altre poesie scientifiche by Franco Buffoni.